2018
DOI: 10.3389/fphys.2018.01371
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Roles of Dietary Selenium Yeast and Tea Polyphenols on Growth Performance and Ammonia Tolerance of Juvenile Wuchang Bream (Megalobrama amblycephala)

Abstract: In order to investigate protective roles of dietary selenium yeast (SY) and tea polyphenols (TPs) on growth of juvenile Wuchang bream (Megalobrama amblycephala) and its resistance under ammonia stress, juvenile Wuchang bream were randomly assigned into four groups: a control group fed basal diets and three treatment groups fed basal diets supplemented with 0.50 mg/kg SY, 50 mg/kg TPs and a combination of 0.50 mg/kg SY and 50 mg/kg TPs, respectively. After 60 days of feeding, growth parameters of Wuchang bream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…In addition, some studies have found that dietary supplementation of Se‐yeast (0.5mg/kg) could effectively improve nitrite resistance in Wuchang bream ( Megalobrama amblycephala ) (Long et al, 2017) and Chinese mitten crab ( Eriocheir sinensis ) (Wang et al, 2019). Guo et al (2018) found that single and combined supplementation of selenium yeast and green tea‐derived polyphenols improved the antioxidant capacity and immune response in juvenile Wuchang bream under ammonia stress. This finding possible implies the possibility of using Se‐yeast as an additive to enhance the immune response and antioxidant capacity during the summer season when the water temperature is usually at a range of 28℃ to 31℃.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have found that dietary supplementation of Se‐yeast (0.5mg/kg) could effectively improve nitrite resistance in Wuchang bream ( Megalobrama amblycephala ) (Long et al, 2017) and Chinese mitten crab ( Eriocheir sinensis ) (Wang et al, 2019). Guo et al (2018) found that single and combined supplementation of selenium yeast and green tea‐derived polyphenols improved the antioxidant capacity and immune response in juvenile Wuchang bream under ammonia stress. This finding possible implies the possibility of using Se‐yeast as an additive to enhance the immune response and antioxidant capacity during the summer season when the water temperature is usually at a range of 28℃ to 31℃.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient Se intake may cause a high death rate, slow growth rate and reduce feed efficiency of juvenile grouper (Lin & Shiau, 2005). On the opposite, excessive Se intake will impair health and decrease cognitive function in several fish species, including loach ( Paramisgurnus dabryanus ) (Hao et al, 2014), white sturgeon ( Acipenser transmontanus ) (Zee et al, 2016), meagre ( Argyrosomus regius ) (Khalil et al, 2018) and Wuchang bream ( Megalobrama amblycephala ) (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GH may boost the local synthesis of IGF-1 that exerts paracrine or autocrine effects [ 23 ]. Subsequently, IGF-1 by acting on target cells, causes them to proliferate and differentiate and ultimately stimulates the growth of the body [ 24 ]. The previous studies on the Nile tilapia showed that there is a positive correlation between IGF-1 protein and mRNA levels in liver and body weight gain and SGR of this fish species [ 25 , 26 ].…”
Section: The Effect Of Phytochemicals and Their Derivatives On Growth-related Genesmentioning
confidence: 99%
“…The total RNA obtained by the TRIzol reagent (Takara, Dalian, China) was reversed transcription with PrimeScript™ RT reagent Kit with gDNA Eraser (Takara, Dalian, China) according to our previous study. 37 The detailed test procedures were supplied in Supporting Information (Test S1). The primers sequences of genes were designed by the Primer Premier 5.0 software or referred to previous studies (Table 1).…”
Section: Gene Expression Analysismentioning
confidence: 99%